Strategi Pengembangan Usahatani Lada di Desa Wonuahoa Kecamatan Lambuya Kabupaten Konawe - Resniatin Gamasa; Ulyasniati Ulyasniati; Idrus Salam (Mikroba : Jurnal Ilmu Tanaman, Sains Dan Teknologi Pertanian, 2025)
The purpose of this study was to determine the internal and external factors of pepper farming development and to identify strategies for developing pepper farming in Wonuahoa Village, Lambuya District, Konawe Regency. This study was conducted from April to June 2024, in Wonuahoa Village, Lambuya District, Konawe Regency. The determination of the location of this study was carried out purposively, a method of determining the research area intentionally. The population in this study were all farmers who farm pepper in Wonuahoa Village, Lambuya District, Konawe Regency, where the number of farmers was 56 people. The sample determination was carried out by census, namely by taking all populations as research samples. The analysis uses the SWOT formula. Based on the results of the study, internal factors (strengths and weaknesses) are strength factors consisting of five strength factors while weakness factors consist of five strength factors and external factors (opportunities and threats) are opportunity factors consisting of six opportunity factors while threat factors are the fourth threat factor in the development of pepper farming in Wonuahoa Village, Lambuya District, Konawe Regency and the strategy for developing pepper farming in the research area shows that pepper farming is in the position of development strategy quadrant I (Aggressive Strategy) namely optimizing the high potential price of pepper in the market determined by certified seeds (S1-O1), The high enthusiasm of farmers will be able to use cultivation technology (S4-O4) and high farmer loyalty will create support from the government (S3-O6)